A comparative study of teaching internship practices: Insights from Can Tho University and Quirino State University - Divina Gracia Sabio; Agaton Pattalitan; Thi Thuy Diem Huynh; Thinh Mai Phuc (CTU Journal of Innovation and Sustainable Development)
This study compares the implementation of teaching internship (TI) guidelines and practices at the School of Education, Can Tho University (CTU), Viet Nam, and the College of Teacher Education, Quirino State University (QSU), the Philippines. Using a qualitative research approach, the study applied Braun and Clarke’s (2006) thematic analysis with Delve Software for coding. Data was collected through document analysis. Findings reveal that while both universities share certain aspects in the implementation of guidelines and practices, notable differences were also observed. These distinctions present valuable opportunities for both institutions to improve and enhance their teaching internship programs.